STUDI KARAKTERISTIK MORFOLOGI BEBERAPA VARIETAS TANAMAN SELADA (Lactuca sativa L.) HASIL INTRODUKSI - Sumiahadi, Ade; Wulandari, Yukarie Ayu; Putri, Dirgahani (Jurnal Agroteknologi, 2024)
Lettuce is a vegetable crop with a demand that continues to increase yearly. This situation is influenced by increasing public awareness of healthy lifestyles and urban farming practices. Diverse genetic sources are essential in plant breeding programs to form varieties with superior characteristics to increase productivity. One of the methods that can be done to improve genetic variation is by introduction. This research aims to study the morphological characteristics of three varieties of introduced lettuce. This research was conducted in the experimental field of the Faculty of Agriculture, Universitas Muhammadiyah Jakarta, from July to November 2022. The study compared three introduced lettuce varieties from Turkiye and three national commercial varieties. The morphological characteristics observed included qualitative (leaf shape, leaf vein shape, leaf tip shape, and leaf colour) and quantitative (crop height, number of leaves, leaf width, leaf length, harvest age, gross weight, and consumption weight). The results showed that only V4 had the same qualitative characteristics as its comparison variety (V1). The results also showed that in terms of quantitative characteristics, V4 and V5 had a higher resemblance to their comparator varieties (V1 and V2, respectively), while V6 had a further similarity to its comparator variety (V3). These introduced varieties have phenotypic variability that can be used as sources of plant genetics for plant breeding programs.